The carbon release triggered by 1.32 Ga sill emplacement and its potential environmental implications - Zhang, Chaokun; Tian, Wei; He, Yanxin; Gong, Mingyue; Li, Shun (Frontiers in Earth Science, 2024)
Magmatic activity is one of the important pathways for the delivery of deep Earth carbon to the surface. The massive carbon release in this process can have significant impacts on atmospheric-oceanic environment. Previous studies have done a lot of work on the relationship between Phanerozoic magmatic activity and carbon release, but there is relatively limited attention has been given to investigating the association between Precambrian magmatic activity and carbon release. The Yanliao Large Igneous Province at 1.32 Ga exhibits extensive development of sills, and the reaction between sills and surrounding rocks triggers the release of carbon. Simultaneously, the magmatic activity during this period is considered as the final response to the breakup of the Columbia supercontinent, coinciding with the occurrence of the Mesoproterozoic Oxygenation Event (MOE).To explore the connection between this magmatic activity and global carbon cycling, environmental changes and planetary evolution, nine representative stratigraphic columns are selected from the Yanliao area. We use the SILLi 1.0 1D model by utilizing the one-dimensional finite element method (FEM) to simulate and estimate the amount of carbon release triggered by sill emplacement. The simulation results indicate that the emplacement of sills increased the surrounding rock temperature and vitrinite reflectance, leading to a decrease in the total organic carbon (TOC) content. A large amount of organic carbon and inorganic carbon was released, which was initiated by the reaction between sills and surrounding rocks, with a total carbon release up to 1.24×10 13 tons. The estimated CO2 equivalent released during this magma activity episode is expected to be greater than 4.58×10 13 . In Mesoproterozoic strata, the emplacement of sills activates carbon within the lithosphere could have implications for the global environment. Further work needs to be done in other ancient cratons that possess Lower Riphean strata to find additional evidence of the impact of this magmatic event on the Earth system. From this study, it is evident that magmatic activity during the Precambrian period could promote the activation of carbon in crustal sediments and influence global environment, which can a reference for people to understand the planetary evolution process.